Academic Motivation and Social Support as Predictors of College Readiness in Post-Pandemic Students - Julianto, Very (Utan Kayu Publishing, 2025)
College readiness refers to students' ability to successfully transition to higher education without requiring remedial coursework. However, the COVID-19 pandemic has introduced new policies in the education sector, particularly the widespread implementation of online learning across all educational levels. This shift has led to limited interaction between students and teachers, negatively affecting students' college readiness. This study aims to investigate the relationship between academic motivation and social support on college readiness in the post-COVID-19 context. A total of 294 respondents participated in this study by completing a questionnaire. The instruments used include the CAYCI Career and College Readiness Scale, the Academic Motivation Scale (AMS), and the Multidimensional Scale of Perceived Social Support (MSPSS). Data were analyzed using linear regression with JAMOVI software version 2.5.3. The results show a significant relationship between academic motivation and social support with college readiness (p 0.001). Consequently, the null hypothesis is rejected. To promote optimal college readiness, it is recommended that schools implement specialized programs focused on college preparation, such as regular academic tutoring, independent learning skills training, and mentoring activities can be implemented as external support mechanisms to strengthen students’ college readiness. Future research should also examine additional factors influencing college readiness among students.